"SCIENTIFIC GENERATION AND LINGUISTIC PARADIGM OF CIVILIZATION XX – XXI CENTURIES." FIRST SCIENTIFIC CONFERENCE DEDICATED TO THE MEMORY OF ACADEMICIAN STEPANOV Y.S. (Proceedings of Southern Federal University. Philology, 2013)
Grigoriyan E.L. This article describes scientific conference dedicated to the memory of Academician Stepanov Y.S. The main aspects of the report were concepts and borrowings, dialectal division of the Indo-European language system, structure of the sentence in the Indo-European languages, bilateral texts, advertising and poetic texts, addressed to children. Participants of the conference shared their memories about Stepanov Y.S.Keywords: concepts, borrowings, linguistics, Indo-European languages, bilateral text, Stepanov Y.S.